Effect of drought stress on oxidative damage and antioxidant enzyme activity in melon seedlings - Kavas, Musa; Baloglu, Mehmet Cengiz; Akca, Oya; Kose, Fatma Selin; Gokcay, Derya (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2013)
Drought stress is one of the most serious environmental limitations affecting the growth and productivity of plants. In the current study, oxidative damage and antioxidant responses under polyethylene glycol (PEG)-induced osmotic stress were compared in 2 melon cultivars, Kirkagac and Galia. Melon seedlings were subjected to PEG-6000 solutions of 2 different osmotic potentials, -0.2 MPa and -0.4 MPa. Various physiological parameters, malondialdehyde (MDA), proline content, and antioxidant enzymes including catalase (CAT), ascorbate peroxidase (APX), and glutathione reductase (GR) were measured. A reduction in fresh and dry weights of shoot and root tissues was observed. Significant proline accumulation was detected with increasing osmotic potential for both cultivars. A significant rise in MDA was detected in Kirkagac at -0.4 MPa osmotic potential. In Galia hydrogen peroxide (H2O2) content increased significantly as PEG concentration increased. CAT showed significantly increased activity only at -0.4 MPa osmotic potential in both cultivars. PEG-induced osmotic stress altered GR activity in both cultivars. These results suggest that (i) Galia is more tolerant than Kirkagac, and (ii) drought tolerance in both cultivars might be closely related to an increase in capacity for antioxidant enzyme activity and the osmoprotective function of proline. Comparing these responses will help to identify drought tolerance mechanisms in melon cultivars.
Keywords: malondialdehyde; Cucumis melo; antioxidant enzymes; drought stress; proline; 2. Zero hunger; 15. Life on land; 6. Clean water